Algeria’s Energy Security Problem between Domestic Consumption Demands and Production Constraints: what Role for Renewable Energies? - Khouazem, Hamza (Finance and Business Economies Review, 2022)
With the aim of diversifying energy sources and ensuring energy security, Algeria is developing renewable energies, providing an important asset of renewable energy sources from solar radiation, wind energy and other sources. In contrast, the Algerian Government's vision is based on a strategy centered on the valuation of inexhaustible natural resources, where it has shown great and growing interest in the field of renewable energy development, through the development of many laws and the launching of an ambitious program that enables it to produce electricity. In addition to entering into foreign partnerships to share experiences and develop renewable energies along the lines of projects programmed to the horizon of 2030, they build a strong economic structure that reflects positively on development, as one of the rich countries in these sources.In this study, we will try to highlight the role of renewable energies in achieving energy security in Algeria by presenting various concepts related to energy security, as well as by examining and analysing the reality of energy production and the evolution of its consumption in Algeria. Finally, the orientations of the national policy for the development of renewable energies and its future prospects are identified as a bet for achieving energy security in Algeria